Penentuan Prioritas Persediaan Barang dengan Menggunakan Hybrid Method - Aldino, Muhammad Satria; Sandiwarno, Sulis (Diponegoro University, 2025)
Warehouse is a facility that serves as storage of goods or products. Inventory of goods has an impact on the continuity of the construction project, because if the material runs out, the contractor cannot carry out the work, as a result the project may be delayed from the predetermined schedule. The purpose of the warehouse is to monitor and control the incoming or outgoing materials in a project. In previous studies, an analysis of the AHP and TOPSIS methods has been carried out, but AHP has problems when used in cases with a large number of criteria and alternatives. While TOPSIS has problems in determining the value of the criteria because it is too subjective. Therefore, in this study we propose a hybrid method for calculating DSS which is called “Analytical Hierarchy – Similarity to Ideal Process” (AH-SIP). This proposed method has goals, namely in determining the value of the criteria with a comparison matrix using AHP, and performing alternative rankings using TOPSIS. The results of this study in determining the best material recommendations for procurement are D 25 Threaded Iron with a preference of 0.777, Chicken Wire with a preference of 0.677, and Pilox with a preference of 0.669.